The performance of laboratory tests in the management of a large outbreak of orally transmitted Chagas disease - Belkisyolé Alarcón de Noya; Zoraida Díaz-Bello; Cecilia Colmenares; Reinaldo Zavala-Jaspe; Teresa Abate; Rosa Contreras; Sandra Losada; Domingo Artigas; Luciano Mauriello; Raiza Ruiz-Guevara; Oscar Noya (Memorias do Instituto Oswaldo Cruz, 2012)
Orally transmitted Chagas disease (ChD), which is a well-known entity in the Brazilian Amazon Region, was first documented in Venezuela in December 2007, when 103 people attending an urban public school in Caracas became infected by ingesting juice that was contaminated with Trypanosoma cruzi. The infection occurred 45-50 days prior to the initiation of the sampling performed in the current study. Parasitological methods were used to diagnose the first nine symptomatic patients; T. cruzi was found in all of them. However, because this outbreak was managed as a sudden emergency during Christmas time, we needed to rapidly evaluate 1,000 people at risk, so we decided to use conventional serology to detect specific IgM and IgG antibodies via ELISA as well as indirect haemagglutination, which produced positive test results for 9.1%, 11.9% and 9.9% of the individuals tested, respectively. In other more restricted patient groups, polymerase chain reaction (PCR) provided more sensitive results (80.4%) than blood cultures (16.2%) and animal inoculations (11.6%). Although the classical diagnosis of acute ChD is mainly based on parasitological findings, highly sensitive and specific serological techniques can provide rapid results during large and severe outbreaks, as described herein. The use of these serological techniques allows prompt treatment of all individuals suspected of being infected, resulting in reduced rates of morbidity and mortality.